Pengujian Efisiensi Pasar terhadap Pengumuman Quick Count saat Proses Pemilihan Umum Presiden dan Wakil Presiden Indonesia tahun 2024 - Tiffany Cheyenne Rachel Adjani; Mahatma Kufepaksi; Igo Febrianto (CV. Aksara Global Akademia, 2025)
Capital market is an important indicator of economic growth, which responsive to political events, including general elections. The Indonesia 2024 presidential elections are a significant political event that can impact the market, particularly as there is no incumbent presidential candidate, increasing political uncertainty. One of the key informational event during the election process is the announcement of the quick count. Although not the official result, it can provide an initial overview of the election results and serve as a reference for market participants. This study aims to determine the market reaction, indicated by significant abnormal returns surrounding the quick count announcement. It also aims to determine the difference in average abnormal returns and average trading volume activity. The sample for this study is 45 companies listed in the LQ45 index, which will be examined as a whole and by sector. The data analysis used in this study was t-test for normally distributed data and nonparametric test for non-normally distributed data. The results of this study indicate significant abnormal returns around the quick count announcement. The t-test results indicate a significant difference in average abnormal returns and trading volume activity before and after the quick count announcement.